PERANCANGAN SISTEM PEMETAAN DIGITAL OBJEK WISATA MANDEH BERBASIS WEB DI KABUPATEN PESISIR SELATAN - anover, iko puji; Irsyadunas, Irsyadunas (Jurnal EDik Informatika, 2019)
Mandeh tourism was inaugurated in June 2015 due to its natural beauty and scenery, but there is still a lack of availability of directions and location plans about the attractions of the Mandeh region. The absence of Mapping in the Mandeh area is in print media, often confusing visitors to the Mandeh area due to lack of guidance. System Development Life Cycle (SDLC) The model used is the waterfall model. SDLC waterfall model waterfall model, provides sequential software flow sequentially. Based on this, a digital mapping system needs to be made that is easy to use by users and does not require much time in processing its use. Digital mapping system that will be created using Adobe Dreamweaver CS6 12.0.0.580 and Xampp 3.2.2.0. In accordance with the title made, which will later produce a mapping system that is effective and efficient and optimizes managers in generating learning.